2023
DOI: 10.3389/fcell.2022.1023418
|View full text |Cite
|
Sign up to set email alerts
|

Tau phosphorylation and PAD exposure in regulation of axonal growth

Abstract: Introduction: Tau is a microtubule associated phosphoprotein found principally in neurons. Prevailing dogma continues to define microtubule stabilization as the major function of tau in vivo, despite several lines of evidence suggesting this is not the case. Most importantly, tau null mice have deficits in axonal outgrowth and neuronal migration while still possessing an extensive microtubule network. Instead, mounting evidence suggests that tau may have a major function in the regulation of fast axonal transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Building upon this foundation, our current study demonstrates that γ-adducin 1–357 fragment enhances tau phosphorylation. It has been reported that over phosphorylation of tau also affects neurite outgrowth ( Morris and Brady, 2022 ). Thus, γ-adducin 1–357 fragment may not only directly influence the formation of actin filaments, but also interfere with neurite outgrowth by enhancing tau phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Building upon this foundation, our current study demonstrates that γ-adducin 1–357 fragment enhances tau phosphorylation. It has been reported that over phosphorylation of tau also affects neurite outgrowth ( Morris and Brady, 2022 ). Thus, γ-adducin 1–357 fragment may not only directly influence the formation of actin filaments, but also interfere with neurite outgrowth by enhancing tau phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data show that axonal GSK3 is not activated by AICD, nor does this kinase mediate its inhibitory effect on FAT. This is of particular interest, as prior studies have documented GSK3β activation in AICD-overexpressing mice [17,18,43] and AD-affected brain tissues [3]. One possible explanation for these different effects of AICD on different pathways in distinct experimental settings is that some effects are restricted or markedly more prominent on specific subcellular compartments.…”
Section: Aicd Impacts Fat Via Activation Of Axonal Kinasesmentioning
confidence: 98%
“…For example, phosphorylation of tau at specific sites can promote activation of a phosphatase-dependent pathway leading to GSK3 activation [36,[44][45][46]. Studies showing AICD-dependent activation of GSK3β or protein kinase A (PKA) all relied on analysis of whole-brain or whole-cell lysates [16][17][18]43,47]. In those studies, the impact of AICD was reported to depend on kinase activation as well as nuclear signaling, and modulation of NMDAR and L-type Ca 2+ channels, which are lacking in the axoplasm [15,16,[48][49][50][51].…”
Section: Aicd Impacts Fat Via Activation Of Axonal Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several modifications cause the adoption of PAD-exposed conformations and/or cause toxicity through PAD-dependent mechanisms, including specific phosphorylation modifications, multimeric aggregates, and mutant forms of tau associated with inherited tauopathies [ 64–66 , 92–95 ]. Furthermore, mimicking phosphorylation of tau at the S199/S202/T205 and PHF-1 epitopes (S396/S404) makes the paperclip structure more compact [ 51 ].…”
Section: Introductionmentioning
confidence: 99%